Auditor Tenure and Audit Quality: Evidence of Mandatory Auditor Rotation in Indonesia - AGUS FREDY MARADONA; SUTRISNO SUTRISNO; GRAHITA CHANDRARIN (The Indonesian Journal of Accounting Research, 2013)
The main objective of this research is to investigate the effect of auditor tenure, both in the audit-firm tenure dimension and in the audit-partner tenure dimension, on audit quality. Debate over auditor rotation has been recurring recently, especially when this requirement is included in the proposed public accountant act. Our study is meant to provide empirical evidence for the debate surrounding the auditor rotation requirements in Indonesia. In this study, we identify the length of auditor tenure from the signature of audit-partner in charge on the independent auditor report. We are able to do so since unlike the U.S., the independent auditor reports in Indonesia expose name and signature of the audit-partner in charge. Using modified Jones model of discretionary accruals as our measure of audit quality, we test our hypothesis on our sample of 1,100 firm-year observations from 212 companies for the period of 1995 to 2001. We find that: (1) audit-firm tenure positively affects audit quality; (2) audit-partner tenure does not affect audit quality; and (3) there is an incremental positive effect of audit-firm tenure on audit quality which cannot be explained by audit-partner tenure. Our results suggest that there is an increase in audit quality along with an increase in audit-firm tenure. However, it also suggests that the results of this research do not support the mandatory audit-firm rotation required by the Indonesian government.